Association of CXCR4, CCR7, VEGF-C and VEGF-D expression with lymph node metastasis in patients with cervical cancer. (July 2017) - Dai, Yifei; Tong, Rui; Guo, Hui; Yu, Tingting; Wang, Chunyan
Abstract: Objective: We attempted to investigate the expression of CXCR4, CCR7, VEGF-C and VEGF-D in cervical cancer specimens, and the association between CXCR4, CCR7, VEGF-C and VEGF-D expression with the clinicopathological parameters of patients with cervical cancer. Study design: 57 tissue microarrays including 9 normal cervical tissues and 48 cervical cancer tissues were purchased from Biomax. The association between CXCR4, CCR7, VEGF-C and VEGF-D expression with the clinicopathological parameters were evaluated. Then immunohistochemistry was used to assess the expression of CXCR4, CCR7, VEGF-C and VEGF-D in cervical cancer specimens. Finally, Spearman correlations were used for the correlation analyses between CXCR4, CCR7, VEGF-C and VEGF-D. Results: We revealed that CXCR4 expression was significantly higher in patients with squamous cell carcinomas ( P = 0.002) and lymph node metastasis ( P = 0.038), while CCR7 expression was significantly elevated in patients with lymph node metastasis ( P = 0.037). VEGF-C expression was markedly up-regulated in patients exhibiting FIGO stage II–III tumors ( P = 0.015) and lymph node metastasis ( P = 0.038), while VEGF-D expression was obviously increased in patients displaying FIGO stage II–III tumors ( P = 0.025), squamous carcinomas ( P = 0.017) and lymph node metastasis ( P = 0.037). The correlation analysis indicated that CXCR4, CCR7, VEGF-C and VEGF-D expression have a significant correlation to each other. Conclusion: These results suggested that CXCR4, CCR7, VEGF-C and VEGF-D expression might have synergistic effects on the lymph node metastasis in patients with cervical cancer.